A Review on DTC-SVM Method with Back-to-Back Converter Connected to the Permanent Magnet Generator and Comparison with DTC in the Matrix Converter - Alireza Siadatan; Soroush Sadeghbayan; Ebrahim Afjei (Majlesi Journal of Electrical Engineering)
In this paper, the direct torque control torque based on space vector modulation (DTC-SVM) for permanent magnet synchronous generator connected to the variable-speed wind power generation system will be discussed. One of the most widely used in industry to convert voltage converters, converters back to back due to the very good features it is used. The main use space vector modulation voltage source inverters and current source is 3-phase. DTC method reduces the limitations and complexity of operation, so the price is Replay torque and flux machines that caused the DTC-SVM method is an alternative to it. The possibility of over-voltage matrix converter there on both sides. In some methods, sampling frequency and high frequency is required in others. The space vector modulation method sampling frequency is far less Direct Torque Control solution is a matrix converter.